Bacteriophage-based decontamination to control environmental colonization by Staphylococcus capitis in neonatal intensive care units: An in vitro proof-of-concept - Chavignon, Marie; Kolenda, Camille; Medina, Mathieu; Bonhomme, Mélanie; Blazere, Leslie; Legendre, Tiphaine; Tristan, Anne; Laurent, Frédéric; Butin, Marine (Frontiers in Cellular and Infection Microbiology, 2022)
In neonatal intensive care units (NICUs), the standard chemical-based disinfection procedures do not allow a complete eradication of pathogens from environmental surfaces. In particular, the clone Staphylococcus capitis NRCS-A, a significant pathogen in neonates, was shown to colonize neonatal incubators. The aim of this study was to evaluate the in vitro effect of a bacteriophage cocktail on NRCS-A eradication. Three bacteriophages were isolated, genetically characterized and assessed for their host range using a collection of representative clinical strains (n=31) belonging to the clone NRCS-A. The efficacy of a cocktail including these three bacteriophages to eradicate the reference strain S. capitis NRCS-A CR01 was determined in comparison or in combination with the chemical disinfectant Surfanios Premium on either dry inoculum or biofilm-embedded bacteria. The emergence of bacterial resistance against the bacteriophages alone or in cocktail was evaluated by growth kinetics. The three bacteriophages belonged to two families and genera, namely Herelleviridae/Kayvirus for V1SC01 and V1SC04 and Rountreeviridae/Andhravirus for V1SC05. They were active against 17, 25 and 16 of the 31 tested strains respectively. Bacteriophage cocktails decreased the bacterial inoculum of both dry spots and biofilms, with a dose dependent effect. The sequential treatment with bacteriophages then Surfanios Premium did not show enhanced efficacy. No bacterial resistance was observed when using the bacteriophage cocktail. This study established a proof-of-concept for the use of bacteriophages to fight against S. capitis NRCS-A. Further investigations are needed using a larger bacterial collection and in real-life conditions before being able to use such technology in NICUs.